The management of achondroplasia in Italy: results from a Delphi panel based on real-world experience - Maghnie, Mohamad; Bruzzi, Paolo; Casilli, Giorgio; Lidonnici, Dario; Scarano, Gioacchino (Frontiers in Pediatrics, 2023)
Background: Achondroplasia is a rare genetic disorder caused by a mutation in the FGFR3 gene, leading to skeletal changes and other systemic complications that greatly impact the patient’s quality of life. There currently are differences in achondroplasia patients’ management among countries and centers within the same country. Method: A group of Italian experts discussed the best practice and the current unmet needs in the management of patients with achondroplasia though a two-round Delphi panel, between September and November 2022. The Delphi survey consisted of 32 questions covering organizational aspects, diagnosis and follow-up, and management of achondroplasia patient, and was shared among 54 experts from 25 different centers in Italy. The consensus was determined on the basis of the percentage of agreement or disagreement to each statement on a 5-point Likert scale. Results: Pediatricians (including specialists in pediatrics, medical genetics, and pediatric endocrinology) orthopedics and medical geneticists were the most represented specialists accounting for 64%, 9% and 9% of participants, respectively. The panel highlighted the need for standardized procedures to identify reference centers, the crucial role of multidisciplinary team, and effective communication among centers (Hub and Spoke model) as the essential organizational features; the importance of genetic counseling, presence of a psychologist, and clear communication during prenatal diagnosis as main points for diagnosis; early intervention by different specialists, personalized care, and promotion of a healthy lifestyle as major points for patient management. Conclusion: To ensure an adequate continuity of care over the whole lifespan of a patient with achondroplasia a shared model for patient management is suggested by Italian specialists.